2019
DOI: 10.25248/reac.e2243.2019
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa de coliformes totais e termotolerantes no rio Salgadinho no município de Juazeiro do Norte, CE

Abstract: Este estudo buscou analisar a qualidade bacteriológica da água do rio Salgadinho no município de Juazeiro do Norte, Ceará, por meio da pesquisa de coliformes totais e termotolerantes. As coletas foram feitas onde é evidente o despejo de resíduos domésticos e industriais, no período de agosto a setembro de 2016 com dez dias de intervalo entre cada uma. O procedimento de análise foi realizado em triplicata, utilizando o método de tubos múltiplos quantitativo ou número mais provável (NMP). Foram confirmados 100% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Centeno et al (2016), in the state of Rio Grande do Sul, also observed that increases in precipitation led to an improvement in water quality. Additionaly, Nunes et al (2019) reported that the presence of thermotolerant coliforms in the aquatic environment of the Salgadinho River (Ceará, Brazil) was indicative of contamination by human feces, which resulted from the lack of basic sanitation in the region. In this sense, Amorim et al (2020), in their study of a hydrographic basin in the state of Alagoas, found that the impaired quality of surface water in water bodies, resulting from the negative influence of anthropogenic actions, mainly arises from the inadequate disposal of effluents.…”
Section: Fig 2 Classification Of the Use And Occupation Of Soil On Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Centeno et al (2016), in the state of Rio Grande do Sul, also observed that increases in precipitation led to an improvement in water quality. Additionaly, Nunes et al (2019) reported that the presence of thermotolerant coliforms in the aquatic environment of the Salgadinho River (Ceará, Brazil) was indicative of contamination by human feces, which resulted from the lack of basic sanitation in the region. In this sense, Amorim et al (2020), in their study of a hydrographic basin in the state of Alagoas, found that the impaired quality of surface water in water bodies, resulting from the negative influence of anthropogenic actions, mainly arises from the inadequate disposal of effluents.…”
Section: Fig 2 Classification Of the Use And Occupation Of Soil On Th...mentioning
confidence: 99%
“…It is crucial that studies like this be conducted since water quality can affect the health and welfare of the community in the long run (Ifabiyi et al 2020). Nunes et al (2019) showed the advantages of using total and thermotolerant coliform indicators as bacteriological markers in aquatic environments; however, their study did not correlate with the satellite images. On the other hand, Costa Santos et al (2019) demonstrated that Landsat images are reliable for assessing land use and occupation dynamics in areas protected by law regarding river preservation.…”
Section: Introductionmentioning
confidence: 99%
“…A predileção de análise dos indicadores nitrito e nitrato em águas superficiais, atua como desígnio respectivamente, na ocorrência de processos biológicos ativos influenciados por poluição orgânica e no escoamento de terras agrícolas para rios e riachos devido ao uso de fertilizantes na agricultura (FONSECA, 2017). Já, o grupo coliforme, por habitar o intestino de mamíferos, inclusive do ser humano, a sua presença no ambiente aquático é indicador de contaminação fecal, sendo considerado o bioindicador básico no parâmetro das legislações relativas à água para consumo humano, bem como, no monitoramento da qualidade de águas destinadas a potabilidade e balneabilidade (NUNES et al, 2019). Em seguida a imagem classificada foi transformada para o formato shapefile, gerando polígonos para as classes identificadas, onde foi quantificada a área de cada classe por trecho ao longo do rio (figura 4).…”
Section: Metodologiaunclassified
“…To this end, a methodology for evaluating the performance of Environmental Health It is understood that the literature has advanced from the perspective of evaluating programs in this category in the State of Ceará. Part of the studies focus on addressing the quality of water for human consumption in terms of microbiological and physical-chemical aspects (Bonfim, 2020;Silva et al, 2020;Formiga et al, 2020;; Rodrigues & Diniz, 2019;Oliveira et al, 2019;Oliveira et al, 2012) and correlating water quality to specific diseases (Barbosa et al, 2019;Macedo et al, 2019;Nunes et al, 2019;Costa, 2018;Pereira et al, 2019); other literature explores environmental constraints in accordance with legal and historical aspects (Abreu, 2021;Filho & Araújo, 2020;Vasconcelos & Mota, 2020;Cavalcante et al, 2019;Gomes & Paula, 2019;Gomes & Pessoa, 2019;Silva & Albuquerque, 2018).…”
mentioning
confidence: 99%